1999
DOI: 10.1177/0092070399274005
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Citizenship: Cultural Antecedents and Business Benefits

Abstract: The article explores the nature of corporate citizenship and its relevance for marketing practitioners and academic researchers. Specifically, a conceptualization and operationalization of corporate citizenship are first proposed. Then, an empirical investigation conducted in two independent samples examines whether components of an organization's culture affect the level of commitment to corporate citizenship and whether corporate citizenship is conducive to business benefits. Survey results suggest that mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
747
2
69

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 921 publications
(881 citation statements)
references
References 87 publications
36
747
2
69
Order By: Relevance
“…So far, research that has taken a micro-level perspective on CSR has shown that working for socially responsible companies is positively related to employees' organizational identification (Carmeli et al 2007), work engagement (Glavas and Piderit 2009), retention (Jones 2010), organizational citizenship behavior (OCB; Jones 2010; Lin et al 2010;Sully de Luque et al 2008), organizational commitment (Maignan et al 1999;Mueller et al 2012;Peterson 2004;Turker 2009b), in-role performance (Jones 2010;Vlachos et al 2014), improved employee relations (Agle et al 1999), and firm attractiveness to prospective employees (Turban and Greening 1997). Another important outcome variable, and one that is of specific interest to the present argument, is employee satisfaction.…”
Section: The Effects Of Csr On Employee Satisfactionmentioning
confidence: 99%
“…So far, research that has taken a micro-level perspective on CSR has shown that working for socially responsible companies is positively related to employees' organizational identification (Carmeli et al 2007), work engagement (Glavas and Piderit 2009), retention (Jones 2010), organizational citizenship behavior (OCB; Jones 2010; Lin et al 2010;Sully de Luque et al 2008), organizational commitment (Maignan et al 1999;Mueller et al 2012;Peterson 2004;Turker 2009b), in-role performance (Jones 2010;Vlachos et al 2014), improved employee relations (Agle et al 1999), and firm attractiveness to prospective employees (Turban and Greening 1997). Another important outcome variable, and one that is of specific interest to the present argument, is employee satisfaction.…”
Section: The Effects Of Csr On Employee Satisfactionmentioning
confidence: 99%
“…Reed et al, 2007). Taking a more generic approach and focusing on relationships within one organization, Maignan et al (1999), for example, found a significant influence of proactive corporate citizenship behaviour on employee commitment, customer loyalty and performance, with customer loyalty favourably affecting performance. How these trickle processes (might) work, however, was not shown.…”
Section: Micro Levelmentioning
confidence: 99%
“…Building upon the work of Carroll (1979), Maignan (1997) suggested an operational definition and developed a measurement tool that has later been validated in the US (Maignan, Ferrell, and Hult 1999) and France (Maignan and Ferrell 2001). The conceptualization is comprised of four dimensions:…”
Section: Corporate Citizenshipmentioning
confidence: 99%
“…Some researchers have seen links between the corporate culture, the orientation to different stakeholders, and the degree of involvement in corporate citizenship activities. For example, the more humanistic the organization's culture is, the more likely the firm is to practice corporate citizenship (Maignan, Ferrell, and Hult 1999): The importance attributed to collaboration and harmony among workers, as well as among the company and its different stakeholders is high. These authors showed that a humanistic orientation permits to improve the relationships between the company and its stakeholders by meeting their expectations in economic, legal, ethical, and discretionary areas.…”
Section: Driving Forces Of Corporate Citizenshipmentioning
confidence: 99%